EXAMINING GREEN ACCOUNTING PRACTICES BASED ON SPIRITUALITY AND LOCAL WISDOM: AN ETHNOMETHODOLOGICAL STUDY - Luh Gede Arieska Dianthy; Endang Ruhiyat; Nofryanti (ZILLZELL MEDIA PRIMA, 2024)
This study examines the implementation of the Green Hotel concept based on Tri Hita Karana at Swarga Suites Berawa, Bali, focusing on Parahyangan, Pawongan, and Pabelasan aspects. The Green Hotel approach seeks to mitigate the hospitality industry's environmental impact through resource efficiency, waste management, and nature conservation. Grounded in Balinese philosophy, Tri Hita Karana integrates environmental, spiritual, and social harmony in interactions with employees, guests, and the local community. Using a qualitative ethnomethodology approach, data were gathered through interviews, observations, and documentation to analyze the concept's application and its impact on financial performance. Results indicate successful implementation, including prayer facilities, preservation of Balinese traditions, and eco-friendly practices. Financially, the hotel showed improvements in liquidity, profitability, and solvency, despite a decline in the Total Asset Turnover Ratio due to long-term investments in green technology. This study underscores the role of Tri Hita Karana in promoting sustainability and highlights its financial benefits, positioning Swarga Suites Berawa as a model for eco-friendly hospitality.